Emotional modulation of statistical learning in visual search - Zinchenko, Artyom; Bierlich, Afton M.; Conci, Markus; Müller, Hermann J.; Geyer, Thomas (Frontiers in Cognition, 2024)
Visual search is facilitated when participants encounter targets in repeated display arrangements. This ‘contextual-cueing’ effect is attributed to incidental learning of spatial distractor-target relations, which subsequently guides visual search more effectively toward the target location. Conversely, behaviorally significant, though task-irrelevant, negative emotional stimuli may involuntarily capture attention and thus hamper performance in visual search. This raises the question of how these two attention-guiding factors connect. To this end, we investigated how an emotionally alerting stimulus induced by different classes of emotional (face, scene) pictures prior to the search task relates to memory-related plasticity. We tested 46 participants that were presented with repeated and non-repeated search layouts, and which were preceded at variable (50, 500, 1000 milliseconds) intervals by emotional vs. neutral faces or scenes. We found that contextual learning was increased with emotional compared to neutral scenes, while no modulation of the cueing effect was observed for emotional (vs. neutral) faces. This modulation occurred independent of the intervals between the emotional stimulus and the search display. We conclude that emotional scenes are particularly effective in withdrawing attentional resources, biasing individual participants to perform a visual search task in a passive, i.e., receptive, manner, which, in turn, improves automatic contextual learning.